The Export Development Process: An Integrative Review of Empirical Models - Leonidou, Leonidas C.; Katsikeas, Constantine S. (Journal of international business studies, 1996)
Despite widespread research on the export behavior of firms, no integrative review of the empirical work in relation to export development models exists in the extant literature. This article reviews the main models on the subject, identifies their structural characteristics, evaluates the methodologies used for their validation, and analyzes the key conceptual issues emerging from their assessment. While valuable inroads into the mechanics and constituent parts of the export development process have been made, this avenue of empirical inquiry has attracted criticism on structural, methodological and conceptual grounds. Future research in the field should harness the eclectic contribution afforded by existing theory and, at the same time, enhance its status with contributions from marketing, business and other disciplines.